Islet1 and Brn3 Expression Pattern Study in Human Retina and hiPSC-Derived Retinal Organoid - Ziming Luo; Chaochao Xu; Kaijing Li; Bikun Xian; Yuchun Liu; Kang Li; Ying Liu; Huifeng Rong; Mingjun Tang; Dongpeng Hu; Sijing Yang; Meifang Ye; et al. (Hindawi Limited, 2019)
This study was conducted to determine the dynamic Islet1 and Brn3 (POU4F) expression pattern in the human fetal retina and human-induced pluripotent stem cell- (hiPSC-) derived retinal organoid. Human fetal eyes from 8 to 27 fetal weeks (Fwks), human adult retina, hiPSC-derived retinal organoid from 7 to 31 differentiation weeks (Dwks), and rhesus adult retina were collected for cyrosectioning. Immunofluorescence analysis showed that Islet1 was expressed in retinal ganglion cells in the fetal retina, human adult retina, and retinal organoids. Unexpectedly, after Fwk 20, Brn3 expression gradually decreased in the fetal retina. In the midstage of development, Islet1 was detected in bipolar and developing horizontal cells. As the photoreceptor developed, the Islet1-positive cone precursors gradually became Islet1-negative/S-opsin-positive cones. This study highlights the distinguishing characteristics of Islet1 dynamic expression in human fetal retina development and proposes more concerns which should be taken regarding Brn3 as a cell-identifying marker in mature primate retina.